ASIL AL-QUR’AN DENGAN PENDAPAT SAHABAT DAN TABI’IN - Zuhry, Saifuddin; Islamiyah, Islamiyah (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2021)
The emergence of various models and methods of interpretation of the Qur'an is one form of effort  disclose text messages optimally according to the abilities and social conditions of the commentator.  The sources of interpretation are based on: the Qur'an itself, the authentic al-Sunnah, the opinions of the Companions and tabi'in, Arabic (because it was revealed using that language), ra'yu and ijtihad in accordance with  Arabic and Shari'ah rules.  And the interpretation that comes from what has been mentioned (al-Qur'an itself, the authentic Sunnah, the opinions of the Companions and tabi'in, Arabic, ra'yu aNd Ijtihad in accordance with Arabic rules), is called  with the Al-Qur'an.  In this journal, we will discuss the Asil al-Qur'an with the opinions of friends and tabi'in sourced from various books.  Regarding the Asil al-Qur'an with the opinion of the companions, there is a dispute about its position.  Some say marfu' and others say mauquf.  While the tabi'in interpretation can essentially be taken and can be used as a legal basis, as long as it is in accordance with the Qur'an and al-Sunnah.